Inhibitors of mTOR and Risks of Allograft Failure and Mortality in Kidney Transplantation. Issue 1 (1st October 2012) - Isakova, T.; Xie, H.; Messinger, S.; Cortazar, F.; Scialla, J. J.; Guerra, G.; Contreras, G.; Roth, D.; Burke, G. W.; Molnar, M. Z.; Mucsi, I.; Wolf, M.
Abstract : Data on long‐term outcomes of users of inhibitors of the mammalian target of rapamycin (mTORI) are lacking in kidney transplantation. In an analysis of 139 370 US kidney transplant recipients between 1999 through 2010, we compared clinical outcomes among users of mTORIs versus calcineurin inhibitors (CNI) in their primary immunosuppresive regimen. During the first 2 years posttransplantation, primary use of mTORIs without CNIs (N = 3237) was associated with greater risks of allograft failure and death compared with a CNI‐based regimen (N = 125 623); the hazard ratio (HR) of the composite outcome ranged from 3.67 (95% confidence interval [CI], 3.12–4.32) after discharge to 1.40 (95% CI 1.26–1.57) by year 2. During years 2–8, primary use of mTORIs without CNIs was independently associated with greater risks of death (HR 1.25; 95% CI, 1.11–1.41) and the composite (HR 1.17; 95%CI, 1.08–1.27) in fully adjusted analyses. The results were qualitatively unchanged in subgroups defined by medical history, immunological risk and clinical course during the index transplant hospitalization. In a propensity‐score matched cohort, use of mTORIs was associated with significantly worse outcomes during the first 2 years and greater risks of death (HR 1.21; 95% CI, 1.05–1.39) and the composite (HR 1.18; 95% CI, 1.08–1.30) in years 2–8. Compared with CNI‐based regimens, use of an mTORI‐based regimen for primary immunosuppression in kidney transplantation was associated with inferior recipient survival. Abstract : The authors conduct an observational study of 139, 370 recipients who underwent kidney transplantation between 1999 and 2010 in the United States and find that compared with calcineurin‐inhibitor‐based regimens, use of mammalian target of rapamycin–based regimens for primary immunosuppression is associated with inferior recipient survivals.